Dilema Hakim Pengadilan Agama dalam Menyelesaikan Perkara Hukum Keluarga Melalui Mediasi - Erie Hariyanto; Moh. Efendi; Sulistiyawati Sulistiyawati (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2021)
This article aims to determine the role of judges in resolving family law cases through mediation in the Religious Courts, where judges have the position as state officials as regulated in Law Number 43 of 1999 concerning Basic Personnel, can also be a mediator in the judiciary. as regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures where judges have the responsibility to seek peace at every level of the trial and are also involved in mediation procedures. The research method used in this article uses normative legal research methods. Whereas until now judges still have a very important role in resolving family law cases in the Religious Courts due to the fact that there are still many negotiating processes with mediation assisted by judges, even though on the one hand the number of non-judge mediators is available, although in each region it is not evenly distributed in terms of number and capacity. non-judge mediator.